Kerajinan ukiran kayu dalam pengaruh Hindu-Buddha dan Islam di Museum Balaputra Dewa Palembang (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
This research aims to describe the art of wood carving which is influenced by Hindu-Buddhist and Islamic culture at the Balaputra Dewa Museum, South Sumatra. Using a descriptive qualitative approach, this research collected data through literature review and direct observation in museums. The literature review included historical books, scientific articles and online sources related to the art of wood carving, while observations were made to observe and record details of the carvings in the museum. The research results show that the wood carvings in this museum depict the influence of Hindu-Buddhist and Islamic culture through decorations that include fauna, flora and geometric motifs, which reflect historical and religious values. This research also emphasizes the importance of preserving the art of wood carving as part of Indonesia’s cultural heritage.
Keywords: Wood Crafts; Wood Carving; Hindu-Buddhist; Islam; Balaputra Dewa Museum